PWE-099 Audit of elective and emergency surgery for crohn's disease at a district general hospital: is there a role for exclusive enteral nutrition and the specialist ibd dietician?. (17th June 2017) - Patel, RN; Corrigall, D; Syme, G; Hay, V; Hammond, T; Saverymuttu, S; Shah, R
Abstract : Introduction: Recent evidence shows that pre-operative exclusive enteral nutrition (EEN) in stricturing and penetrating Crohn's disease is associated with better outcomes after surgery (1). We have audited our use of pre-operative EEN in Crohn's disease patients at a large district general hospital (DGH) over a 5 year period and described outcomes in both emergency and elective admissions. Method: We present the demographics and outcomes of adult patients with Crohn's disease who had resections over a 5 year period (Jan 2012 to Dec 2016) at a DGH in south east England. To obtain the electronic discharge summaries we used the diagnosis and procedure codes for 'Crohn's disease' and 'Digestive Tract' from the ICD-10 and OPCS classification of surgical operations and procedures, respectively. We reviewed whether patients were seen by a dietician in the 6 months prior to surgery or if EEN was trialled within 6 weeks of surgery. Results: Distribution of Crohn's disease; Small bowel 32 (39%), Crohn's colitis 32 (39%), Ileo-colonic 18 (22%). Type of surgery; Small bowel resection 20 (24.4%), Ileo-colonic resection 24 (29.3%), Right/Left hemicolectomy 17 (20.7%), Proctectomy=5 (6.1%), Subtotal colectomy 4 (4.9%), Total colectomy 9 (11%), Panproctocolectomy 3 (3.7%). Table to compare Crohn's patients who underwent surgical resection, divided by type of admission. Conclusion: Only 1 in 8 patients are being treated with EEN prior to surgery at our centre. Collaboration with a specialist IBD dietician and introduction of a formal pre-operative EEN protocol will be offered to optimise patients before surgery. The ratio of elective to emergency surgery (1:1) indicates a need for a more proactive approach in preparing patients for operative intervention to reduce complications and prolonged admissions. References: . Heerasing N. et al. Exclusive enteral nutrition provides an effective bridge to safer interval elective surgery for adults with Crohn's disease. Aliment Pharmacol Ther. 2017Mar;45(5):660–669. Disclosure of Interest: None Declared